Pengaruh Pembiayaan Bermasalah, Perputaran Kas, Dan Utang Jangka Pendek Terhadap Likuiditas PT Bank Muamalat Indonesia - Nabil Ahmad Izzudin; Lili Puspita Sari (Universitas Pembangunan Nasional Veteran Jakarta, 2022)
Liquidity indicates the bank's ability to meet the possibility of withdrawing funds made by customers. In this study, liquidity can be measured using the financing to deposit ratio (FDR). This study aims to determine the effect of financing, cash turnover, and short-term debt on the liquidity of PT Bank Muamalat Indonesia. In this study, the independent variables are Non-performing Financing, Cash Turnover, and short-term debt, the dependent variable is liquidity. This research method used in this study is the Classical Assumption Test, Multiple Linear Regression Analysis and Hypothesis Testing.The results of this study show that non-performing financing, cash turnover, and short-term debt have a negative effect on liquidity. . In addition, based on the t test, the results showed that the variables indicated problematic financing, cash turnover, and short-term debt had a partial effect on liquidity.